2022
DOI: 10.2141/jpsa.0210116
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Effect of Dietary Oregano Extracts and 3,4,5-Trihydroxy Benzoic Acid on Growth Performance and Elimination of Coccidiosis in Broiler Chickens

Abstract: We aimed to compare the combinatorial effect of 3,4,5-trihydroxybenzoic acid (THB) and oregano extracts (OE) with THB alone on the growth performance and elimination of deleterious effects in coccidiosis-infected broilers. A total of 210 one-day-old broilers were randomly assigned to one of five dietary treatments, with six replicates each, for 35 days. Dietary treatments were: 1) non-challenged, non-treated (NC); 2) challenged, non-treated (PC); 3) PC+ Salinomycin (0.05 g/kg; AB); 4) PC+THB (0.1 g/kg; THB); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
2
1
0
Order By: Relevance
“…Then, a higher oocyst output, a depressed growth rate, and a lower carcass yield were observed in those extra-challenged broilers at 18 d of age. These results agreed with previous studies ( Abdelhady et al, 2021 ; Nawarathne et al, 2022 ). Furthermore, the current study indicated that the coccidial challenge at an early age has a detrimental effect on meat quality at a later age (color, pH, protein content, cook loss).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Then, a higher oocyst output, a depressed growth rate, and a lower carcass yield were observed in those extra-challenged broilers at 18 d of age. These results agreed with previous studies ( Abdelhady et al, 2021 ; Nawarathne et al, 2022 ). Furthermore, the current study indicated that the coccidial challenge at an early age has a detrimental effect on meat quality at a later age (color, pH, protein content, cook loss).…”
Section: Discussionsupporting
confidence: 94%
“…Our data indicated that both oregano oil and clove oil improved broiler growth performance including weigh gain and feed conversion ability, which was consistent with previous studies ( Nawarathne et al, 2022 ; Zaazaa et al, 2022 ; Youssefi et al, 2023 ). Although broilers are considered to have less sense of taste than other mammalian production animals due to the shortage of sweet sensing gene T1R2 ( Shi and Zhang, 2006 ), essential oils could improve broiler nutrient utilization through other mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Supplementing poultry feed with natural products containing bioactive components has shown promising results (Alagawany et al, 2019;Gado et al, 2019;El-Hack et al, 2020;Liu et al, 2022). The coccidial inhibitory effect of 3,4,5-trihydroxybenzoic acid can be enhanced by the addition of oregano extracts to improve animal performance and eliminate adverse effects in coccidiosis-infected broilers for 34 days (Nawarathne et al, 2022). Several of the approximately 200 species of the genus Rumex are considered good sources of traditional medicines for the treatment of inflammation, cancer, and various bacterial infections due to bioactive compounds, particularly quercetin 3-O-glucoside, nepodin, emodin, trans-resveratrol, and torachryson (Vasas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%